CoNi bimetallic alloy cocatalyst-modified g-C3N4 nanosheets for eﬃcient photocatalytic hydrogen production. (November 2021) - Lu, Congrong; Wu, Enci; Li, Chunhe; Dou, Weidong; Lian, Yuan; Liang, Yulan; Xiang, Xiaoyan; Wang, Hongmei
Abstract: Non-precious and Earth-abundant cocatalysts have emerged as promising alternatives to precious metal catalysts for hydrogen generation from photocatalytic water splitting. In this work, CoNi/g-C3 N4 photocatalyst composed of g-C3 N4 nanosheets and CoNi alloyed nanoparticles was prepared by a simple solvothermal and chemical reduction method. Bimetallic CoNi alloy was found to accelerate charge transfer and inhibit electron and hole recombination, thereby enhancing the photocatalytic activity of CoNi/g-C3 N4 . Under optimal conditions, the hydrogen production rate of CoNi/g-C3 N4 reached up to 354.4 μmol h −1  g −1 with visible light (λ > 420 nm) in triethanolamine aqueous solution; this value greatly exceeded that of g-C3 N4 by a factor of 188 times. A mechanism explaining the excellent photocatalytic performance was proposed accordingly. These results suggest that g–C3 N4 –based photocatalysts have good potential for hydrogen generation. Highlights: CoNi/g-C3 N4 nanocomposites are fabricated using a simple method. CoNi/g-C3 N4 nanocomposites enhance visible light absorption. CoNi bimetal alloy can effectively enhance the separation of charges. CoNi/g-C3 N4 exhibits excellent photocatalytic hydrogen production.